Evaluation of the effect of some denture cleansers on the colour of acrylic resin denture base materials - Munther N Kazanji; Zina M Ahmad (University of Mosul, College of Dentistry, 2004)
The aims of this study were to evaluate the effect of denture cleansers on the colour of acrylic resin denture base material, and to evaluate the effect of particle size and surface roughness of acrylic resin material on their colour change. Sixty four acrylic specimens were prepared from the three types of acrylic resin materials of 30×20×1.5 mm (length× wid-th× thickness, respectively). After the con-ditioning in distilled water, they were immersed in eight types of denture cleansers for 7 days. The colour changes were asse-ssed using a computerized ultraviolet-visible spectrophotometer with accuracy up to 0.001. Visual examination of colourchange was done by three independent examiners. The analy sis of particle size was per-formed with a sieving machine. The sur-face roughness of acrylic specimens was measured using a computerized surface texture measuring and recording machine (Perthometer). A statistical analysis was performed using analysis of variance and Duncan's Multiple Range Test. The results revealed that there was a significant difference at p  0.01 between the tested solutions and also between the three types of acrylic resin materials. It was concluded that denture cleansers induced colour change of acrylic resin denture base materials. The self-curing acrylic exhibited the highest colour change. The smaller particle size and the smoothest surface of resin materials decreased the amount of colour change.